Efficiency of human capital use in agriculture at the present stage of development (Journal of Economic Research & Business Administration, 2018)
The article presents the results of theoretical review and materials generalization on the interpretationof human capital essence and it’s role. It is the main strategic resource capable of solving complexproblems of the country’s transition to a «green economy». Human capital is considered by us as a setof certain personal, social, professional, business qualities, and is an important investment resource, theuse of which contributes to the improvement of production efficiency. Considerable attention is paid tomethodological aspects of human capital research. Despite the importance of productive use problemof human capital, the interrelationship of quality, personnel motivation and efficiency of its use is insufficientlyresearched, which caused the need for a more detailed research of this issue with the use ofselective, monographic studies, statistical methods of researching stochastic connections. The researchincludes the following stages: analysis and assessment the level of human capital development in Kazakhstanagainst the background of developed foreign countries, identificate the factors affecting the use of this capital and the calculation of their relationship strength; formation of proposals for the accumulation,effective use and further human capital development in the agricultural sector.